Institutional violence and disability: punishing conditions - Rossiter, Kate (Routledge advances in disability studies, 2019)
Introduction -- The institutional cases & the conditions for moral abdication -- The institutional violence continuum -- Thoughtlessness & violence as work culture -- Quantifying & re-inscribing violence -- Embedded trauma & embodied resistance -- Conclusion